AN ANALYSIS OF PROSPECTIVE PRIMARY SCHOOL TEACHERS’_x000D_ INTERCULTURAL SENSITIVITY IN TERMS OF DIFFERENT_x000D_ CULTURAL VARIABLES - (:unkn) unknown (My University, 2020)
This study aims to analyse prospective primary school teachers’ levels of intercultural sensitivity in Turkeyaccording to the variables of national cultural differences and experiencing the differences at national levelsocially. Causal-comparative research model and Simple random sampling method were used in the study. 387undergraduate students attending the primary School Teaching Departments of Ziya Gökalp Faculty ofEducation of Dicle University and Atatürk Educational Faculty of Marmara University were included in thisresearch. The data was collected by the Intercultural Sensitivity Scale (ISS). Descriptive statistics were used inthe analysis of the data independent sample t-test and one-way ANOVA. As a result, it was found thatprospective primary school teachers are at satisfactory levels in terms of intercultural sensitivity. Additionally,intercultural sensitivity levels of prospective primary school teachers using two or more languages incommunication with their family members or relatives were significantly higher than those using one language.

Bu çalışmada sınıf öğretimeni adaylarının kültürler arası duyarlılık düzeylerinin ulusal kültürel farklılıklar ve bu_x000D_ farklılıkları ulusal düzeyde deneyimleme değişkenlerine göre incelemek amaçlanmaktadır. Araştırmada nedensel_x000D_ karşılaştırma araştırma modeli ile basit rasgele örneklem tekniği kullanılmıştır. Araştırmaya Dicle Üniversitesi_x000D_ Ziya Gökalp Eğitim Fakültesi ile Marmara Üniversitesi Atatürk Eğitim Fakültesinde öğrenim gören 387 sınıf_x000D_ öğretmeni adayı katılmıştır. Çalışmada veriler kültürler arası duyarlılık ölçeği ile toplanmıştır. Verilerin_x000D_ analizinde bağımsız gruplar t- testi ve one-way anova testleri kullanılmıştır. Araştırma bulgularına göre sınıf_x000D_ öğretmeni adaylarının kültürler arası duyarlılık seviyesi yeterli düzeydedir. Bunun yanında akrabaları veya aile_x000D_ üyeleri ile iletişiminde iki veya daha fazla dil kullanan sınıf öğretmeni adaylarının kültürler arası duyarlılık_x000D_ düzeyi tek dil kullananlara göre anlamlı olarak daha yüksektir.
SINIF ÖĞRETMENİ ADAYLARININ KÜLTÜRLERARASI DUYARLILIK DÜZEYLERİNİN FARKLI KÜLTÜREL DEĞİŞKENLER AÇISINDAN INCELENMESİ